KAJIAN TERMINOLOGI TUJUAN PENDIDIKAN - Suryadi, Rudi Ahmad (Dirasa Islamiyya: Journal of Islamic Studies, 2023)
The purpose of education is an important component in educational studies. The purpose of education leads to the achievement of something that is achieved by individuals after carrying out education. In this case, the formulation of educational goals leads to what conditions are expected in the educational process. The expected conditions or goals to be achieved will of course be different according to one's outlook on life as well as the will of the country where he lives. The goals of education in one country are also different from the goals of education in other countries. However, even though the formulation of educational goals in various countries is different, there is one goal that is agreed upon, namely that human beings are intelligent, skilled, and become good citizens. The research used the library study method. Documentation techniques are carried out in order to obtain a complete picture of the text being searched for. The results of the research showed that in the study of the terminology of objectives, there are at least several terms associated with the meaning of these objectives. In English, the terms objective, aim, purposes and goals are known; whereas in Arabic the terms ghâyah, hadf, and maqâshid are also known. In this case the use of the term must be appropriate in accordance.